DEVELOPMENT OF PROFESSIONAL AND ETHICAL COMPETENCE OF FUTURE PRESCHOOL EDUCATION TEACHERS - Khabibullaeva Sayyorakhon Makhamadali qizi (Sciental Journals Publishing, 2025)
This article provides a scientific and theoretical justification for the necessity of forming and developing the professional-ethical competence of future preschool education teachers. It highlights the essence of pedagogical competence, the importance of professional-ethical values, personal responsibility, and moral stance. The professional and ethical qualities of the teacher’s personality and the components of competence formed on their basis are analyzed. Based on existing academic sources, the main factors and directions for developing this competence are presented.
Keywords: Professional-ethical competence, preschool education, preschool teacher, moral values, pedagogical activity, professionalism, pedagogical responsibility, professional stance.